Aflibercept or bevacizumab in combination with FOLFIRI as second-line treatment of mRAS metastatic colorectal cancer patients: the ARBITRATION study protocol. (March 2021) - Ottaiano, Alessandro; Scala, Stefania; Santorsola, Mariachiara; Trotta, Anna Maria; D'Alterio, Crescenzo; Portella, Luigi; Clemente, Ottavia; Nappi, Anna; Zanaletti, Nicoletta; De Stefano, Alfonso; Avallone, Antonio; Granata, Vincenza; et al.
Background: The intensive study of predictive factors has strongly ameliorated the therapeutic flow-chart of metastatic colorectal cancer (mCRC) by allowing the selection of patients who benefit from specific therapies. For instance, in mRAS (mutated RAS) mCRC patients, anti-EGFR drugs (cetuximab and panitumumab) are not recommended; in this group of patients, the use of anti-angiogenic drugs (bevacizumab and aflibercept) is predominant. However, at progression to standard bevacizumab-based first-line chemotherapy, still to date, there are no studies to guide oncologists in the choice of the best second-line anti-angiogenic drug (bevacizumab beyond progression versus aflibercept). Methods: ARBITRATION is a prospective, observational study assessing efficacy differences between second-line fluorouracil/irinotecan (FOLFIRI)/bevacizumab versus FOLFIRI/aflibercept at progression to fluoropyrimidines, oxaliplatin and bevacizumab in mRAS mCRC patients. A test power of 80%, a median survival of 9 months from second-line treatment start and a hazard ratio of 0.67 between the two schedules were the basis for statistical design. The final sample will be 220 patients (110 per treatment). The significance will be verified with a two-tailed log-rank test with an alpha value of the I-type error of 5%. Time-to-outcome will be described by Kaplan–Meier curves and prognostic factors studied through multivariable analyses based on the Cox model. Secondary objectives include safety, responses' duration and progression-free survival. A translational research will be conducted to measure several angiogenic proteins in patients' serum before starting the therapy in order to evidence any angiogenic factor patterns related to outcome. Discussion: We present a large, prospective, observational study aiming to answer two scientific questions: (1) outcome differences between second-line treatments with FOLFIRI/bevacizumab beyond progression versus FOLFIRI/aflibercept in mRAS mCRC patients, (2) angiogenic factors' patterns that could associate with efficacy and help oncologists to apply best the therapeutic anti-angiogenic strategies. Trial registration: The ARBITRATION trial (version 0.0, 13 April 2020) has been registered into the clinicaltrials.gov registry on 20 May 2020 with identifier NCT04397601.